AN ANALYSIS OF THE FIFTH SEMESTER STUDENTS’ SPEAKING FLUENCY OF ENGLISH STUDY PROGRAM OF RIAU UNIVERSITY - Muhammad Marjan; Mahdum '; Syafri K. ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was about speaking fluency level of the fifth semester students of English Study Program of Riau University. This is a descriptive quantitative research with 2 minutes recorded speech as primary data. 24 students were chosen from population of 75 students. The cluster random sampling was used to choose the students from 3 different classes.. The speeches were analysed through 2 steps: Spectrograms analysis & statistical analysis. The study showed that a small number of students speaking fluency level in English Study Program of Riau University are still in level Intermediate and although most students are categorized Good, at least the number of who are in level Advance is three times bigger then those in Intermdiate. Despite of the fact the students’s speaking fluency can be concluded as good, the writer would like to recommend other researchers to conduct similar research upon other speaking fluency test so that we can compare it for deeper analysis, more objective and holistic picture speaking fluency.Key Words : Fluency, Speaking, Objective